2000
DOI: 10.1051/analusis:2000280455
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of nitric oxide, nitrite and nitrate using a chemiluminescence assay:an update for the year 2000

Abstract: This review deals with the measurement of nitric oxide (NO) using the chemiluminescence assay. A preliminary discussion is offered to explain the chemical basis for this assay and emphasize the importance of measuring NO. After reviewing some practical aspects and caveats of the chemiluminescence assay, we review its application in a variety of research and clinical settings, such as measurement of breath NO and serum nitrates. The importance of avoiding confounding effects of dietary nitrates when assessing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Using a gas-phase chemiluminescent assay based on the chemiluminescent properties of NO 2 · formed from NO that reacts with ozone ( Mc Murtry et al , 2000 ), Planchet et al (2006) reported that cryptogein caused no or only a weak NO emission which appeared several hours after elicitor addition to the cell suspensions. This result strongly differs from the present electrochemical data.…”
Section: Discussionmentioning
confidence: 99%
“…Using a gas-phase chemiluminescent assay based on the chemiluminescent properties of NO 2 · formed from NO that reacts with ozone ( Mc Murtry et al , 2000 ), Planchet et al (2006) reported that cryptogein caused no or only a weak NO emission which appeared several hours after elicitor addition to the cell suspensions. This result strongly differs from the present electrochemical data.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly developed techniques are chemiluminescence, UV-visible spectroscopy, fluorescence, electron paramagnetic resonance spectroscopy (EPR) and electrochemistry. [12][13][14][15][16][17][18][19][20] While each technique has certain individual advantages, all of them have disadvantages that limit their application. These disadvantages range from lack of sensitivity or specificity to interference from other species commonly present in biological systems.…”
Section: Damien Quintonmentioning
confidence: 99%
“…EPR spectroscopy is also widely used for NO detection through the development of several methods of NO-trapping [17], but its heaviness and poor detection limit (1 mM) make it unsuitable for routine uses. Finally, gas phase chemiluminescence assay [18], based on the chemiluminescent properties of excited NO Ã 2 formed from NO that reacts with ozone, offers real utility and ease for some specific applications, especially for NO exhaled gas. It may be considered as the most rapid assay available.…”
Section: Introductionmentioning
confidence: 99%